Literature Review: Evaluasi Pelatihan Pemberian Makan Bagi Bayi dan Anak (PMBA) dalam Meningkatkan Pengetahuan dan Keterampilan Peserta sebagai Upaya Pencegahan Stunting - Lestari, Faetria; Adhani, Rosihan; Rahman, Fauzie; Isa, Mohammad (Universitas Malahayati, 2026)
ABSTRACT According to the World Health Organization (WHO) and the United Nations Children's Fund (UNICEF), more than 50% of infant and toddler deaths are related to malnutrition, and two-thirds of these deaths are related to inappropriate feeding practices for infants and children. The purpose of PMBA training is for health workers, health cadres, and the general public to be able to provide the right food for infants and children. The policy related to PMBA has been running for a long time, the Ministry of Health has issued PMBA guidelines since 2021 which refers to Presidential Decree No. 72 of 2021 concerning the acceleration of stunting reduction. There is a need to evaluate PMBA training, one of which is to improve the knowledge and skills of participants. To analyze the effectiveness of Infant and Child Feeding Counseling Training (PMBA) for health workers in improving the knowledge and skills of participants. A literature review was conducted through the following databases: Google Scholar in the period 2021 to 2025, in English or Indonesian. Articles were selected based on full texts that met the inclusion and exclusion criteria. Articles were compiled using the PRISMA (Preferred Reporting Items for Systematic Review and Meta Analysis) guidelines. PMBA training can significantly improve participants' knowledge in proper feeding for infants and children. PMBA training is an effective program in providing proper feeding for infants and children as an effort to reduce the incidence of stunting in Indonesia. Keywords: PMBA Training, Knowledge, Skills, Nutrition. ABSTRAK Menurut World Health Organization (WHO) dan United Nations Children’s Fund (UNICEF), lebih dari 50% kematian anak balita terkait dengan keadaan kurang gizi, dan dua pertiga diantaranya kematian tersebut terkait dengan praktik pemberian makan yang kurang tepat pada bayi dan anak. Dilakukannya pelatihan PMBA bertujuan agar tenaga Kesehatan, kader Kesehatan, maupun Masyarakat umum dapat memberikan makanan yang tepat bagi bayi dan anak. Kebijakan terkait PMBA sudah berjalan sejak lama, Kemenkes telah menerbitkan pedoman PMBA sejak tahun 2021 yang mengacu pada Perpres no 72 Tahun 2021 tentang percepatan penurunan stunting. Perlunya dilakukan evaluasi pelatihan PMBA, salah satunya dalam meningkatkan pengetahuan dan keterampilan peserta. Menganalisis efektifitas Pelatihan Konseling Pemberian Makan Bayi dan Anak (PMBA) pada tenaga Kesehatan dalam meningkatkan pengetahuan dan keterampilan peserta. Tinjauan literatur dilakukan melalui basis data: Google Scholar dalam rentang tahun 2021 hingga 2025, berbahasa inggris atau indonesia. Artikel dipilih berdasarkan teks lengkap yang sesuai dengan kriteria inklusi dan ekskusi. Artikel disusun menggunakan panduan PRISMA (Preferred Reporting Items for Systematic review and Meta Analysis). pelatihan PMBA secara signifikan dapat meningkatkan pengetahuan peserta dalam pemberian makan yang tepat pada bayi dan anak. Pelatihan PMBA merupakan program yang efektif dalam pemberian makan yang tepat bagi bayi dan anak sebagai upaya menekan kejadian stunting di Indonesia. Kata Kunci: Pelatihan PMBA, Pengetahuan, Keterampilan, Gizi.